Secularism: Soviet style ; teaching atheism and religion in a Volga republic - Luehrmann, Sonja (New anthropologies of Europe, 2011)
Neighbors and comrades: secularizing the Mari country -- "Go teach": methods of change -- Church closings and sermon circuits -- Marginal lessons -- Visual aid -- The soul and the Spirit -- Lifelong learning -- Conclusion: affinity and discernment